2011
DOI: 10.1097/dbp.0b013e318208f576
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Its Association With Obesity-Specific Health-Related Quality of Life

Abstract: Objective To (1) describe type and source of social support perceived by obese youth and examine associations with sociodemographic/anthropometric characteristics, and (2) examine relationships between social support and obesity-specific health-related quality of life (HRQOL). Methods Seventy-four obese youth and their primary caregivers participated. Youth completed the Child and Adolescent Social Support Scale and an obesity-specific HRQOL measure, Sizing Me Up. Results Close friends and parents provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
5
45
1
2
Order By: Relevance
“…This result may be due to the fact that depressive symptoms were significantly correlated (r = −0.49) with ISEL scores, and these depressive symptoms, in turn, may have been confounded with the significant association between social support and obesity-specific HRQOL. On the other hand, Herzer et al reported that perceived social support was significantly associated with obesity-specific HRQOL in obese youth; this significant association may differ from ours because of different sources of support, i.e., close friends, parents, and teachers (Herzer et al 2011). Further research is needed using various social support measures among overweight and obese individuals to identify the association between social support and HRQOL.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This result may be due to the fact that depressive symptoms were significantly correlated (r = −0.49) with ISEL scores, and these depressive symptoms, in turn, may have been confounded with the significant association between social support and obesity-specific HRQOL. On the other hand, Herzer et al reported that perceived social support was significantly associated with obesity-specific HRQOL in obese youth; this significant association may differ from ours because of different sources of support, i.e., close friends, parents, and teachers (Herzer et al 2011). Further research is needed using various social support measures among overweight and obese individuals to identify the association between social support and HRQOL.…”
Section: Discussionmentioning
confidence: 91%
“…The total score of BDI-II ranges from 0-63 and is categorized by: 0-13 for minimal, 14-19 for mild, 20-28 for moderate, and 29-63 for severe depressive symptoms. The BDI-II has high internal consistency (Cronbach's alpha = 0.91), and an average test-retest reliability of 0.72 across 20 studies (Herzer et al 2011). In this study, the Cronbach's alpha was 0.88.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The presence of a correlation between high BMI and social support is highlighted and the support of family, close friends, and teachers is especially underlined (44,45). Social support promotes healthy behaviors; therefore, increasing social support from family and friends is warranted (44). Social support was found to be directly related with well-being, whereas BMI was not (41).…”
Section: Discussionmentioning
confidence: 99%
“…Controversial results have been obtained in studies related to the effect of social support on BMI and weight loss (41)(42)(43)(44)(45). The presence of a correlation between high BMI and social support is highlighted and the support of family, close friends, and teachers is especially underlined (44,45). Social support promotes healthy behaviors; therefore, increasing social support from family and friends is warranted (44).…”
Section: Discussionmentioning
confidence: 99%